COORDINATION CONTROLLER POWER SYSTEM IN JAVA-BALI 500 KV INTERCONECTED BASED ON BACTERIA FORAGING - PARTICLE SWARM OPTIMIZATION FOR STABILITY IMPROVEMENT - IBG Manuaba; AAN Amrita; Ardyono Priyadi; Hery Purnomo (Universitas Trunojoyo Madura, 2015)
Power system stabilizer (PSS) and flexible AC transmission system (FACTS) damping controller to improve the stability of the power system has been widely used. A coordinated control method based on the combined computational evolutionary theory is proposed to overcome some of damping controllers simultaneously so as to keep the allowable level of power system damping. It works by making full use of favorable interaction between the controlling and minimizing adverse interactions so that the power system oscillations can be suppressed effectively. Proportional integral derivative (PID) controller tuning based power system stabilizer types PSS3B (PIDPSS3B), static var compensator (SVC) and automatic voltage regulator (AVR) presented in this paper. PID controller gain parameters such as proportional, integral factor, differential coefficient and get AVR selected and optimized by BF-PSOTVAC. The integral time absolut error (ITAE) standards of optimization design as objective function. The results of simulations show that performance index of system the proposed method is 42.7890. The BF-PSOTVAC method has the capability to damping optimally and suppresses error to minimum.